TEACHING AND RESEARCH: TOWARDS THE DEVELOPMENT OF A CULTURE OF RESEARCH TRAINING - Rodríguez de Los Ríos, Luis (2014)
This communication addresses one of the most significant issues of the contemporary university, the same that is related to the absence of a research culture from an institutional perspective, especially in the vast majority of public universities. It is proposed as a formative research of alternative strategies for the development of a research culture, describing relevant teaching methodologies. Also, it emphasizes the relationship between teaching and research as essential functions of the university.